2020
DOI: 10.1016/j.ajo.2020.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Retinopathy Secondary to Maternally Inherited Diabetes and Deafness – Evaluation of Predicting Parameters

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
(54 reference statements)
4
15
0
Order By: Relevance
“…A recently published autofluorescence study of MIDD observed that retinal degeneration developed at eccentricities of 10 to 20 degrees with foveal sparing, unlike in other macular dystrophies, which typically affect the center. 19 This feature was also observed in our patients, although the fovea was affected in both eyes of P1 and the right eye of P3. We hypothesize that this parafoveal atrophy and foveal sparing may in part be due to a higher heteroplasmy levels of the mutation specifically in the cells at eccentricities of 10 degrees to 20 degrees as compared to the rest of the retina, or due to the varied expression of antioxidant enzymes described in proteomic analyses of these anatomic regions in the RPE and retina.…”
Section: Comparison Of Disease Phenotypes Between Midd and Ksssupporting
confidence: 85%
See 4 more Smart Citations
“…A recently published autofluorescence study of MIDD observed that retinal degeneration developed at eccentricities of 10 to 20 degrees with foveal sparing, unlike in other macular dystrophies, which typically affect the center. 19 This feature was also observed in our patients, although the fovea was affected in both eyes of P1 and the right eye of P3. We hypothesize that this parafoveal atrophy and foveal sparing may in part be due to a higher heteroplasmy levels of the mutation specifically in the cells at eccentricities of 10 degrees to 20 degrees as compared to the rest of the retina, or due to the varied expression of antioxidant enzymes described in proteomic analyses of these anatomic regions in the RPE and retina.…”
Section: Comparison Of Disease Phenotypes Between Midd and Ksssupporting
confidence: 85%
“…In recent studies of MIDD, Müller et al have hypothesized that RPE atrophy may precede photoreceptor death in MIDD, and by extension mitochondrial diseases, based upon a combination of longitudinal SW-AF and SD-OCT analysis, which revealed a delay between RPE atrophy and subsequent visual acuity loss and retinal thinning as seen on SD-OCT. 19,20 In our cohort, we observed a number of additional features that support this hypothesis in both MIDD and KSS.…”
Section: Additional Features Suggestive Of Primary Rpe Diseasesupporting
confidence: 74%
See 3 more Smart Citations